2018
DOI: 10.1007/s11657-018-0450-8
|View full text |Cite
|
Sign up to set email alerts
|

A low phase angle measured with bioelectrical impedance analysis is associated with osteoporosis and is a risk factor for osteoporosis in community-dwelling people: the Yakumo study

Abstract: The phase angle is a predictor of osteoporosis, which is unaffected by age and sex, and a lower phase angle is associated with greater probability of osteoporosis. The phase angle can be easily measured, and osteoporosis can be confirmed even at home. This may facilitate early diagnosis and treatment, which may be useful for preventing diseases related to osteoporosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 29 publications
2
20
0
Order By: Relevance
“…A lower phase angle is generally considered a prognostic predictor or an early predictor of various diseases [3, 28, 29]. We have similarly found that a low phase angle is associated with LS and osteoporosis [46]. All these suggested the correlation between low phase angle and frailty that we found.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…A lower phase angle is generally considered a prognostic predictor or an early predictor of various diseases [3, 28, 29]. We have similarly found that a low phase angle is associated with LS and osteoporosis [46]. All these suggested the correlation between low phase angle and frailty that we found.…”
Section: Discussionsupporting
confidence: 76%
“…The phase angle was measured using BIA. We used the InBody 770 BIA unit (InBody Co., Ltd., Seoul, Korea) to perform the BIA [46]. The accuracy of this device has been reported previously [15, 16].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many previous reports involving biomarkers and predictors for osteoporosis [4, 1519]. Bone resorption biomarkers, bone formation biomarkers, and regulators of bone turnover have all been implicated in previous research, and procollagen type 1 N-terminal propeptide has been identified as a sensitive and stable bone biomarker for the early detection of osteoporosis [4].…”
Section: Discussionmentioning
confidence: 99%
“…A water-bath ultrasound system (model A-1000 Plus II; Lunar, Madison, WI, USA) was used for the measurement of bone status parameters in the calcaneus region of the independent foot [ 16 ]. Stiffness (automatically calculated from broadband ultrasound attenuation and sound speed), T -score, percentage young adult mean (YAM), Z -score, and percentage age-matched value were recorded using a standard protocol provided by the manufacturer.…”
Section: Methodsmentioning
confidence: 99%